Christmas Island National Park marine life. - Australia. Director of National Parks ([Christmas Island] : Director of National Parks, 2007)
The Christmas Island Marine Life brochure presents some of the most common species of marine life which can be found in the ocean and reef surrounding Christmas Island, including corals, molluscs, cephalopods, algae, sponges, bryozoans, ascidians, reef fishes, sea jellies, hydroids, Anemones, turtles, crustaceans and echinoderms.
Also available in an electronic version via the Internet at: http://www.environment.gov.au/parks/publications/christmas/marine-brochure.html.
Keywords: National parks and reserves -- Christmas Island (Indian Ocean); Marine organisms -- Christmas Island (Indian Ocean); Marine invertebrates -- Christmas Island National Park; Marine animals -- Christmas Island (Indian Ocean); Marine ecology -- Christmas Island (Indian Ocean); Christmas Island National Park -- Guidebooks